ANALISIS MEKANISME MONEY CHANGER MENURUT FATWA DSN-MUI NO.28/DSN-MUI/III/2002 - Nadin Andini Utami; Fadli Hariadi (AL-INTIFA, 2024)
The sale and purchase of foreign currency in Islam is Al-Sharf which is a currency sale, where money is used as the object of the exchange. Al-Sharf has been regulated in the DSN MUI Fatwa No. 28/DSN-MUI/III/2002 on Currency Sale and Purchase. Buying and selling Foreign Exchange is currently starting to develop and is considered by some people as an alternative business because it can facilitate international buying and selling transactions and bring profits to the perpetrators. This study aims to determine the mechanism of buying and selling sharia currency (Ash-Sharf) according to the Fatwa DSN-MUI. This type of research is library research. This library research is in order to find valid data to be used to collect the intended data as well as systematic discussion and analysis. The results of this study indicate that the practice of buying and selling foreign currencies (Al-Sharf) according to fiqh mu'amalah is permissible if done on the basis of the willingness of both parties and in cash (spot) and it is not allowed to add similar goods (gold with gold or silver with silver).